Gamers' Experience on Incidental Language Learning by Playing Defense of the Ancient 2 - Hapsari, Astri; Sari, Rr Putri Intan Permata; Rais, Burhanudin (IJIE (Indonesian Journal of Informatics Education), 2018)
As information and communication technology (ICT) plays more important role in recent years, the use of ICT tools and media is more common in learning language. One of ICT media  that is promising for language learning is online games because they facilitate incidental language learning as they inherently form part of reading, listening, speaking, and writing. This case study aims to investigate the opinion of gamers about the use of online game Defense of the Ancient 2 (DoTA 2) to learn language. Data were collected through field observation, semi-structured interview, and documentation. Two participants were interviewed.  The findings of this research is that DoTA 2 supports incidental English language learning because it is easy to use and understand the langauge in the game platform;  the content encourages gamers to use English so that gamers learn new vocabularies and practice their English reading skill while playing; the social interaction through chat room and voice chat in planning strategies encorage gamers to communicate in English; the enjoyment from the motivation to win the game makes gamers practice English in team strategy discussion. However, DoTA 2 only focuses on the action of strategies to win the game rather than intended interaction to learn language.